Leiomyosarcoma of scrotum: case report - Bouhout, Tariq (Pan Afr Med J, 2018)
Scrotal leiomyosarcoma is rare tumor. It presents as a painless, slow-growing cutaneous lesion. It’s often mistaken for a benign condition. It is best treated by wide local excision. A case of scrotum leiomyosarcoma is presented in a 63 year old patient who was treated for the first time as having a benign lesion.